Steady-State Auditory Evoked Potentials in Workers Exposed to Occupational Noise - Kamita, Mariana Keiko; Rocha, Clayton Henrique; Silva, Liliane Aparecida Fagundes; Samelli, Alessandra Giannella; Matas, Carla Gentile (La Medicina del Lavoro, 2025)
Background: The present study aims to investigate neural synchrony, as measured by Auditory Steady State Response (ASSR), in individuals with normal hearing who are exposed and not exposed to occupational noise, thereby providing insights into hidden hearing loss within the central auditory nervous system, and justifying the importance of exploring auditory neural function in populations at risk. Methods: A cross-sectional study involved 30 noise-exposed individuals in the Study Group and 30 unexposed individuals in the Control Group, all paired by an average age of 35 years. The following procedures were performed on all individuals: clinical and occupational history, meatoscopy, immitanciometry, pure tone audiometry, speech audiometry, and ASSR (40Hz). We analyzed the audiometric hearing thresholds at frequencies of 1 kHz and 4 kHz, the electrophysiological thresholds estimated by ASSR, and the comparison of the differences between them: the thresholds estimated by ASSR and the audiometry thresholds. The data were analyzed using both descriptive and inferential statistics. P-values ≤ 0.05 were considered significant. Results: When comparing hearing thresholds at 1 kHz and 4 kHz between groups, we found significant differences, with the SG showing higher hearing thresholds than the CG bilaterally. No significant differences were seen in the electrophysiological thresholds estimated by ASSR, nor in the comparison between the ASSR-estimated threshold and the psychoacoustic hearing threshold groups. Conclusions: The results of this study suggest that workers exposed to occupational noise did not show detectable changes in neural synchrony in the midbrain, thalamus, or primary auditory cortex when compared to individuals without occupational noise exposure.